Holographic model of craniosynostosis for HoloLens - Mauricio Mitsuru Yoshida; André Luiz Pires de Freitas; José da Conceição Carvalho Júnior; Julio Sergio de Souza; Vinicius Santos Baptista; Lydia Masako Ferreira (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: To develop a holographic skull model of a deformity resulting from craniosynostosis for the HoloLens. Methods: The methodology for product creation and prototyping was the design thinking structured with the double diamond. A desk survey was conducted with a literature review and an anteriority search. Based on the desk survey results, brainstorming was performed to develop solutions to improve the surgeon’s performance in craniosynostosis using mixed reality. Results: Reports or scientific articles relating mixed reality use to craniosynostosis were not found in search engines or bibliography databases. A surgeon’s performance potential improvement was observed using mixed reality as an auxiliary tool in craniosynostosis surgery. A craniosynostosis skull hologram was developed in mixed reality, with interactivity commands controlled by gestures, facilitating a three-dimensional spatial understanding of cranial anatomy. Conclusion: A holographic skull model with a deformity resulting from craniosynostosis was developed for the HoloLens.